Regeneração in vitro da palma forrageira (Opuntia ficus-indica L. Miller) via embriogênese somática direta - Gomes, Francisco Linhares Arruda Ferreira (2004)
Direct somatic embryogenesis was induced, as the first step towards the development of an efficient genetic transformation system, on shoot apical meristem of prickly-pear (Opuntia ficus-indica L. Miller), when cultured on semisolid MS basal medium supplemented with 4 rnq.l" picloram, 20 g.r1 sucrose and solidified with 7 g.l-1 agar in absence of light, for up to six weeks. Fruits and cladodes were collected from a farm at Canindé county, CE, Brazil during the dry season of 2002 (July - November). The experiments were carried out in the Laboratory of Molecular Biology at the Department of Biochemistry and Molecular Biology of the Federal State University. Several types of explants were used. Explant type, age, physiological status, auxin (type and concentration), light incubation regime and sucrose concentration influenced significantly the outcome of somatic embryo production. The somatic embryos exhibited ali stages of normal zygote embryo development, i.e. from globular to cotyledonary stage. A histological study of somatic embryo development was carried out where it was seen that the somatic embryos, probably of unicellular origin, arose directly from the surface of explants without any intervening callus phase. Typical plantlets were obtained from in v itro maturated and germinated embryos on MS basal medium supplemented with 0.01 rnq.l" picloram and 0.5 rnq.l" BA and solidified with 7 g.I-1 agar. The direct and unicellular origin of the somatic embryos atlained here opens the possibility of producing unique transgenic prickly pear genotypes in subsequent transformation experiments. To the best of our knowledge, this study presents the first detailed description of the ontogeny and in vitro regeneration of directed-derived somatic embryo in the Cactaceae family.